A novel templates of piperazinyl-1, 2-dihydroquinoline-3-carboxylates: Synthesis, anti-microbial evaluation and molecular docking studies. Issue 7 (15th April 2018) - Banu, Saleha; Bollu, Rajitha; Naseema, Mohammad; Gomedhika, P. Mary; Nagarapu, Lingaiah; Sirisha, K.; Kumar, C. Ganesh; Gundasw, Shravan Kumar
Graphical abstract: A series of piperazinyl-1, 2-dihydroquinoline carboxylates have been synthesized in good to excellent yields and screened for their in vitro antimicrobial activities. Compounds9b and10c were identified as promising leads showing good antimicrobial profile. Highlights: A series of piperazinyl-1, 2-dihydroquinoline-3-carboxylates were synthesized. Screened for their in vitro antimicrobial activities. 9b and10c were shown significant. In silico study active with Staphylococcus aureus dehydrosqualene synthase. Abstract: A series of piperazinyl-1, 2-dihydroquinoline carboxylates were synthesized by the reaction of ethyl 4-chloro-1-methyl-2-oxo-1, 2-dihydroquinoline-3-carboxylates with various piperazines and their structures were confirmed by 1 H NMR, 13 C NMR, IR and mass spectral analysis. All the synthesized compounds were screened for their in vitro antimicrobial activities. Further, the in silico molecular docking studies of the active compounds was performed to explore the binding interactions between piperazinyl-1, 2-dihydroquinoline carboxylate derivatives and the active site of the Staphylococcus aureus (CrtM) dehydrosqualene synthase (PDB ID:2ZCQ ). The docking studies revealed that the synthesized derivatives showed high binding energies and strong H-bond interactions with the dehydrosqualene synthase validating the observed antimicrobial activity data. Based on antimicrobial activity and docking studies, the compounds9b and10c were identified as promising antimicrobial lead molecules. This study might provide insights to identify new drug candidates that target the S. aureus virulence factor, dehydrosqualene synthase.